Successful Repair of Concomitant Acute Type A Aortic Dissection and Saddle Pulmonary Embolism - Ramponi, Fabio (Aorta (Stamford), 2018)
Patients presenting with acute onset of chest pain require prompt diagnosis and rapid establishment of a management plan. Acute aortic dissection and acute pulmonary embolism are life-threatening emergencies that can mimic each other at presentation. Correct identification of this uncommon scenario is crucial to initiate the appropriate interventions. The authors present a unique case of concomitant acute type A aortic dissection and acute saddle pulmonary embolism; the patient underwent successful aortic repair and pulmonary embolectomy.